Insecticide and Fungicide Wheat Seed Treatment Improves Wheat Grain Yields in the U.S. Southern Plains. Issue 1 (1st April 2014) - DeVuyst, Eric A.; Edwards, Jeff; Hunger, Bob; Weaver, Lance
Abstract : Hard red winter wheat ( Triticum aestivum L.) in the U.S. Southern Plains is subject to yield losses due to a wide range of pests. Foliar‐applied pesticides are commonly used to control damaging insect populations, but rescue application of foliar pesticides generally occurs at or above threshold infestation levels, commonly leading to yield losses. Further, excessive precipitation, high winds, or producer labor constraints can delay foliar application beyond economically‐optimal thresholds. Insecticide seed treatment offers a method to potentially reduce wheat yield losses due to pest infestations and avoid timing and efficacy issues sometimes associated with foliar applications. Many wheat seed treatments also include a fungicide that protects wheat yield by enhancing seedling emergence, increasing early‐season vigor, and preventing or reducing fall establishment of fungal diseases such as leaf rust. Our purposes here were to investigate the impact of insecticide and fungicide seed treatment on grain yield, grain volume weight, and economic return of hard red winter wheat in Oklahoma. A three‐year study (2008, 2011, and 2012) was conducted at three to five western Oklahoma locations per year. In addition to seed treatment, stocker cattle were used to graze at some locations during winter months, and our analyses also considered the impact of winter grazing on yield, test weight, and economic return.